Determining the long-term changes in biodiversity and provisioning services along a transect from Central Europe to the Mediterranean. - Colombaroli, Daniele; Tinner, Willy (Holocene, 2013)
Climate, land use and fire are strong determinants of plant diversity, potentially resulting in local extinctions, including rare endemic and economically valuable species. While climate and land use are decisive for vegetation composition and thus the species pool, fire disturbance can lead to landscape fragmentation, affecting the provisioning of important ecosystem services such as timber and raw natural resources. We use multi-proxy palaeoecological data with high taxonomic and temporal resolution across an environmental gradient to assess the long-term impact of major climate shifts, land use and fire disturbance on past vegetation openness and plant diversity (evenness and richness). Evenness of taxa is inferred by calculating the probability of interspecific encounter (PIE) of pollen and spores and species richness by palynological richness (PRI). To account for evenness distortions of PRI, we developed a new palaeodiversity measure, which is evenness-detrended palynological richness (DE-PRI). Reconstructed species richness increases from north to south regardless of time, mirroring the biodiversity increase across the gradient from temperate deciduous to subtropical evergreen vegetation. Climatic changes after the end of the last ice age contributed to biodiversity dynamics, usually by promoting species richness and evenness in response to warming. The data reveal that the promotion of diverse open-land ecosystems increased when human disturbance became determinant, while forests became less diverse. Our results imply that the today’s biodiversity has been shaped by anthropogenic forcing over the millennia. Future management strategies aiming at a successful conservation of biodiversity should therefore consider the millennia-lasting role of anthropogenic fire and human activities. [ABSTRACT FROM AUTHOR]
The following values have no corresponding Zotero field: publisher: Sage Publications, Ltd.
Keywords: climate; ecosystem services; evenness-detrended palynological richness; fire; land use; plant diversity

The role of holm oak edges in the control of disturbance and conservation of plant diversity in fire-prone landscapes - Azevedo, J.C. C C; Possacos, a.; Aguiar, C.F. F F; Amado, a.; Miguel, L.; Dias, R.; Loureiro, C.; Fernandes, P.M. M M (Forest Ecology and Management, 2013)
Holm oak (Quercus rotundifolia) woodlands have been able to persist in ﬁre-prone landscapes in northern Portugal where they seem to play a relevant role in community and landscape level patterns and processes, namely in the control of disturbance events and in the maintenance of biodiversity. In this research we tested the following hypotheses: (i) holm oak woodlands affect ﬁre behavior, mainly by disrupting and delaying ﬁre spread; (ii) disruption and delaying of ﬁre spread is due to ﬁre extinction at the edge of woodlands; and (iii) plant diversity is favored by frequent low-intensity ﬁres as a result of the control of ﬁre spread by holm oak woodland edges. We sampled herbaceous, shrub and tree structure and herbaceous plant composition across edges of holm oak woodlands with known recent contact with ﬁre. Using BehavePlus we converted structural data into fuel models and simulated ﬁre behavior for the locations sampled along the exterior–interior gradient of the woodlands. Our results indicate that holm oak woodlands play a relevant role in the control of ﬁre spread and in the maintenance of plant diversity. We found differences in simulated maximum rate of ﬁre spread (ROS) and ﬁreline intensity (FLI) between outside and inside woodlands as well as a 100% probability of ﬁre extinction when fuel moisture was >12% and wind speed at 10 m aboveground was <40 km h1 , supporting the self-extinction hypothesis. We found also that richness and abundance of herbaceous plants varied between the interior and exterior of the woodland, with higher values outside the woodland, and that plant composition along the interior– exterior gradient had distinct patterns. These variables and the pattern of plant distribution were also signiﬁcantly affected by time since last ﬁre event. We conclude that holm oak woodlands affect ﬁre behavior by interrupting ﬁre spread at the edge zone and that ﬁre-created edges affect herbaceous plant species richness, abundance and distribution by maintaining habitat diversity, which increased plant diversity at patch and landscape levels. Based on our results and other evidence, we developed a conceptual model of the dynamics of ﬁre, landscape structure, and plant diversity in ﬁre-prone landscapes where holm oak patches persist.
Keywords: Edges; Fire behavior; Mediterranean Region; plant diversity; Portugal; Quercus rotundifolia

Short-term effects on sheep pastureland due to grazing abandonment in a Western Mediterranean island ecosystem: A multidisciplinary approach - Farris, Emmanuele; Filigheddu, Rossella; Deiana, Pietrino; Farris, Giovanni a; Garau, Giovanni (Journal for Nature Conservation, 2010)
Changes of pasture communities consequent to management practices resulting from land abandonment considerably affect the structure and function of the ecosystem. This study analyses the consequences of grazing abandonment in terms of plant and soil microbial diversity and fertility, on a Mediterranean upland sheep pasture, over a short period (ﬁve years). Grazing was experimentally excluded by fencing ten 10 10 m permanent plots within an area that had supported grazing until 2000, by 0.23 sheep ha 1 . Plant and soil microbial communities and physicochemical parameters were monitored within the fenced and unfenced control plots, during three sampling times from 2000 (before the fencing) to 2005. Grazing cessation notably altered the ﬂoral composition, with an average dissimilarity of 96.7% between the vegetation communities, over ﬁve years. No signiﬁcant change occurred in the control plots that were grazed throughout the sampling period. This work highlighted that, over a short term, the structural change in the speciﬁc plant composition affected only the grass species, conﬁrming that grazing favours the small-sized species over the annual species. Further, it was evident that species groups of conservational and phytogeographic interest, like the endemic and Mediterranean-Atlantic species, tended to disappear with pasture abandonment and were substituted by more widespread species throughout the Mediterranean or even the world. Pasture abandonment was accompanied by an increase of soil pH and a decrease in soil organic matter and soil nitrogen. The microbial parameters recorded at three different sampling times revealed a substantial effect of the plant community, or the time of grazing abandonment, on soil microbial abundance and diversity. Considerable importance is given to the consequences of pasture abandonment on the conservation of plant and microbial diversity and on soil fertility.
The following values have no corresponding Zotero field: publisher: Elsevier
Keywords: animal-plant interactions; Habitat directive; Land-use change; Mediterranean basin; Microbial community; plant diversity; Poetea bulbosae; Soil fertility

Estimation of plant diversity at landscape level: a methodological approach applied to three Spanish rural areas - Ortega, M (Environmental Monitoring and Assessment, 2004)
Approaches linking biodiversity assessment with landscape structure are necessary in the framework of sustainable rural development. The present paper describes a methodology to estimate plant diversity involving landscape structure as a proportional weight associated with different plant communities found in the landscape mosaic. The area occupied by a plant community, its patch number or its spatial distribution of patches are variables that could be expressed in gamma plant diversity of a territory. The methodology applies (1) remote sensing information, to identify land cover and land use types; (2) aspect, to discriminate composition of plant communities in each land cover type; (3) multi-scale ﬁeld techniques, to asses plant diversity; (4) afﬁnity analysis of plant community composition, to validate the stratiﬁed random sampling design and (5) the additive model that partitions gamma diversity into its alpha and beta components. The method was applied to three Spanish rural areas and was able to record 150–260 species per ha. Species richness, Shannon information index and Simpson concentration index were used to measure diversity in each area. The estimation using Shannon diversity index and the product of patch number and patch interspersion as weighting of plant community diversity was found to be the most appropriate method of measuring plant diversity at the landscape level.
Keywords: landscape; Mediterranean vegetation; metrics; plant diversity; Remote sensing

Estimation of plant diversity at landscape level: a methodological approach applied to three Spanish rural areas - Ortega, M. (Environmental Monitoring and Assessment, 2004)
Approaches linking biodiversity assessment with landscape structure are necessary in the framework of sustainable rural development. The present paper describes a methodology to estimate plant diversity involving landscape structure as a proportional weight associated with different plant communities found in the landscape mosaic. The area occupied by a plant community, its patch number or its spatial distribution of patches are variables that could be expressed in gamma plant diversity of a territory. The methodology applies (1) remote sensing information, to identify land cover and land use types; (2) aspect, to discriminate composition of plant communities in each land cover type; (3) multi-scale ﬁeld techniques, to asses plant diversity; (4) afﬁnity analysis of plant community composition, to validate the stratiﬁed random sampling design and (5) the additive model that partitions gamma diversity into its alpha and beta components. The method was applied to three Spanish rural areas and was able to record 150–260 species per ha. Species richness, Shannon information index and Simpson concentration index were used to measure diversity in each area. The estimation using Shannon diversity index and the product of patch number and patch interspersion as weighting of plant community diversity was found to be the most appropriate method of measuring plant diversity at the landscape level.
Keywords: landscape; Mediterranean vegetation; metrics; plant diversity; Remote sensing

Plant species diversity, plant biomass and responses of the soil community on abandoned land across Europe: idiosyncracy or above belowground time lags - Hedlund, K; Regina, I Santa; der Putten, W H Van (Oikos, 2003)
We examined the relationship between plant species diversity, productivity and the development of the soil community during early secondary succession on former arable land across Europe. We tested the hypothesis that increasing the initial plant species diversity enhances the biomass production and consequently stimulates soil microbial biomass and abundance of soil invertebrates. We performed ﬁve identical ﬁeld experiments on abandoned arable land in ﬁve European countries (CZ, NL, SE, SP and UK) which allowed us to test our hypothesis in a range of climate, soil and other environmental factors that varied between the experimental sites. The initial plant diversity was altered by sowing seed mixtures of mid-successional grassland species with two or ﬁve grass species, one or ﬁve legumes and one or ﬁve forbs. The results of low and high sown diversity treatments were compared with plots that were naturally colonized by species present in the seed bank. In three out of the ﬁve ﬁeld sites, there was no correlation between plant species number and plant biomass production, one site had a positive and the other a negative relation. Treatments with a high diversity seed mixture had a higher biomass than the naturally colonized plots. However, there was no signiﬁcant difference between high and low sown diversity plots at four out of ﬁve sites. The three-year study did not give any evidence of a general bottom-up effect from increased plant biomass on biomass of bacteria, saprophytic fungi or abundance of microarthropods. The biomass of arbuscular mycorrhizal was negatively related to plant biomass. The abundance of nematodes increased after abandonment and was related to plant biomass at four sites. Our results support the hypothesis that plant species diversity may have idiosyncratic effects on soil communities, even though studies on a longer term could reveal time lags in the response to changes in composition and biomass production of plant communities.
Keywords: Microbial biomass; plant biomass; plant diversity; soil community (voyant)